Prediction of general and violent recidivism among mentally disordered adult offenders: test of the level of service/risk-need-responsivity (LS/RNR) instrument - Canales, Donaldo D. (Criminal justice and behavior, 2014)
The present investigation examined the predictive validity of the Level of Service/Risk-Need-Responsivity (LS/RNR) instrument for general and violent recidivism in a sample of 138 community-supervised adult mentally disordered offenders. The General Risk/Need section was strongly predictive of general recidivism, whereas the Specific Risk/Need section most strongly predicted violent recidivism. Among males, the General Risk/Need section produced a large effect size for general recidivism, whereas general and violent outcomes for females were best predicted by the Specific Risk/Need section. Across diagnostic subgroups, the General and Specific Risk/Need sections predicted general but not violent recidivism; however, many subgroups were small, highlighting a need for replication research with larger samples. The Other Client Issues and Special Responsivity Considerations sections did not significantly inform recidivism prediction. Broadly interpreted, the overall pattern supports the LS/RNR instrument as valid for use with mentally disordered offenders.